Dynamic response analysis of a catamaran installation vessel during the positioning of a wind turbine assembly onto a spar foundation. (September 2018) - Jiang, Zhiyu; Li, Lin; Gao, Zhen; Halse, Karl Henning; Sandvik, Peter Christian
Abstract: Installation of floating wind turbines is a challenging task. The time and costs are closely related to the installation method chosen. This paper investigates the performance of an efficient installation concept – a catamaran wind turbine installation vessel. The vessel carries pre-assembled wind turbine units including towers and rotor nacelle assemblies. Each unit is placed onto a pre-installed offshore support structure (in this paper a spar floater) during installation. The challenge is to analyse the responses of the multibody system (catamaran-spar-wind turbine) under simultaneous wind and wave loads. Time-domain simulations were conducted for the coupled catamaran-spar system with mechanical coupling, passive mooring system for the spar, and dynamic positioning control for the catamaran. We focus on the steady-state stage prior to the mating process between one turbine unit and the spar, and discuss the effects of wind loads and wave conditions on motion responses of the catamaran and the spar, relative motions at the mating point, gripper forces and mooring forces. The relative motion at the mating point is less sensitive to the blade orientation, but influenced by the wave conditions. Under the investigated sea states, the present installation method shows decent performance. Highlights: Modelling and analysis of a novel concept for installation of floating wind turbines is presented. The multibody system involves a catamaran vessel, a spar platform, sliding grippers, mooring system, and dynamic positioning. Dynamic behaviour of the coupled system is identified under complex environmental conditions. The stage when the wind turbine assembly is being positioned above the spar platform is emphasised.